(untitled) - Sohon, Harry; Harry Sohon (New York, 2002)
This book is intended for use as a supplemental tool for courses in engineering mathematics, applied ordinary and partial differential equations, vector analysis, applied complex analysis, and other advanced courses in which MAPLE is used. Each chapter has been written so that the material it contains may be covered in a typical laboratory session of about 1-1/2 to 2 hours. The goals for every laboratory are stated at the beginning of the chapter. Mathematical concepts are then discussed within a framework of abundant engineering applications and problem-solving techniques using MAPLE. Each chapter is also followed by a set of exploratory exercises that are intended to serve as a starting point for a student's mathematical experimentation. Since most of the exercises can be solved in more than one way, there is no answer key for either students or professors
Keywords: Engineering mathematics